Computer supported cooperative work in design II 9th International Conference, CSCWD 2005, Coventry, UK, May 24-26, 2005: revised selected papers - International Conference on Computer Supported Cooperative Work in Design (Lecture notes in computer science ;, 2006)
This book constitutes the thoroughly refereed post-proceedings of the 9th International Conference on Computer Supported Cooperative Work in Design, CSCWD 2005, held in Coventry, UK, in May 2005. The 65 revised full papers presented were carefully reviewed and selected from numerous submissions during at least two rounds of reviewing and improvement. They contain expanded versions of the papers presented at the conference and are organized in topical sections on CSCW techniques and methods, Grids and Web services, agents and multi-agent systems, ontology and knowledge management, collaborative design and manufacturing, enterprise collaboration, workflows, and other related approaches and applications.